2012
DOI: 10.1074/jbc.m112.393157
|View full text |Cite
|
Sign up to set email alerts
|

BRICHOS Domains Efficiently Delay Fibrillation of Amyloid β-Peptide

Abstract: Background: Alzheimer disease (AD) is associated with A␤ protein misfolding and aggregation into fibrils rich in ␤-sheet structure. Results: BRICHOS domains prevent fibril formation of A␤ far below the stoichiometric ratio. Conclusion: A␤ is maintained as an unstructured monomer in the presence of BRICHOS. Significance: BRICHOS domain can have a natural protective role against A␤ aggregation, which may open new routes toward AD therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(173 citation statements)
references
References 66 publications
9
164
0
Order By: Relevance
“…With respect to Aβ(1-40), GKN1 exibits its anti-Aβ aggregation activity at substoichiometric concentrations (1:10 rGKN1/Aβ molar ratio), in accord with data reported for the recombinant proSP-C and BRI2 BRICHOS domains 28,29 . Regarding the activity of GKN1 toward Aβ(1-42), no data is yet available however, it might be possible that GKN1 behaves similarly to Bri2 and pro-SP-C BRICHOS domains 29 . It must be pointed out that Aβ(1-42) represents the most AD-relevant amyloid peptide 30 .…”
Section: Gkn1 and The Anti-amyloidogenic Property Of Brichos Domainsupporting
confidence: 70%
“…With respect to Aβ(1-40), GKN1 exibits its anti-Aβ aggregation activity at substoichiometric concentrations (1:10 rGKN1/Aβ molar ratio), in accord with data reported for the recombinant proSP-C and BRI2 BRICHOS domains 28,29 . Regarding the activity of GKN1 toward Aβ(1-42), no data is yet available however, it might be possible that GKN1 behaves similarly to Bri2 and pro-SP-C BRICHOS domains 29 . It must be pointed out that Aβ(1-42) represents the most AD-relevant amyloid peptide 30 .…”
Section: Gkn1 and The Anti-amyloidogenic Property Of Brichos Domainsupporting
confidence: 70%
“…Sub-stoichiometric amounts of recombinant BRICHOS domains of human proSP-C and Bri2 prevent fibril formation of both A␤ 40 and A␤ 42 in vitro (37). Recently, it was shown that proSP-C BRICHOS specifically inhibits the secondary nucleation of A␤ 42 aggregation (47).…”
Section: Mode Of Action Of the Brichos Domainmentioning
confidence: 99%
“…The proSP-C BRICHOS domain hence may be a chaperone tailored to interact with a particularly amyloidogenic sequence (34,35). Other BRICHOS homologues possess similar chaperone activity (36,37). Most importantly, the BRICHOS-containing Bri2 protein (also known as ITM2B), which is expressed in the central nervous system, is closely linked to protein aggregation diseases.…”
Section: Brichos: a Multi-purpose Anti-amyloid Chaperonementioning
confidence: 99%
See 1 more Smart Citation
“…In our experiment, the lag time was calculated by fitting established equations to the curve. 34 The ThT fluorescence data, which represented the kinetics in the presence and absence of seeds, showed that gel fibrils did not affect the aggregation of WT α-Syn protein. In contrast, preformed fibril seeds from full-length protein aggregated WT α-Syn protein much faster, as evidenced by the undetectable lag time (Figure 3b).…”
Section: Toxicity and Seeding Capacity Of Amyloid Hydrogelsmentioning
confidence: 99%